The lujanian legacy of ameghino: A stratigraphic revision of the pleistocene-holocene deposits of the río luján valley in its type section. The paleoclimatic record in the pampas from OIS 4 to OIS 1 - Toledo, M.J. (2011)
Between 1870 and 1884, Florentino Ameghino consecrated all his efforts to document and to prove the coexistence of man and Pampean megafauna in the Luján valley. He described several sites in channel and alluvial plain settings in valleys incised on Pampean loess. The geoarchaeological context of these sites, characterized by the abundance of megafauna modified bones, were never studied again after the publication of La Antigüedad del Hombre en el Plata in 1880-81. Here we present a stratigraphical reevaluation and reinterpretation of his "Piso Lujanense" based on a sequence stratigraphy analysis and AMS, OSL and ESR dating. We conclude that the Pleistocene valley fill spans from OIS 4 to OIS 2 with sequence boundaries at 75, 55, 30, 17 and 13 ky BP, reflecting the OIS 4 to OIS 2 glacioeustatic falls in the pampas valleys. These deposits were sealed by a rich organic matter layer or black mats, indicating an abrupt climatic change with a dramatic increase of humidity starting sometime between 12.5 and 13 ky BP. The associated ecological changes probably triggered the extinction process.